Recognition from World Bank - Reliance Industries Limited (2022)
Reliance was adjudged as India’s finest composite textile mill by developed country standards by a visiting team from the World Bank. Japan Textile News reported independently, 'Such a scene is hardly seen even in the highly advanced textile-producing countries like Japan.'